2006
DOI: 10.1080/00029157.2006.10401548
|View full text |Cite
|
Sign up to set email alerts
|

An Early Nineteenth Century Absorption-Based Theory of Mesmerism

Abstract: In 1844, an obscure and little-remembered American theorist, A. Yorke (no further identification is available), published a theory of mesmerism based on absorption, i.e., mental concentration. Unlike Mesmer's conceptualization of animal magnetism as a biological fluid, however, Yorke's theory emphasized the psychological importance of the mutual interaction between mesmerist and subject. This paper discusses the latter's theory of absorption as an important development in neo-mesmerism, the circumstances that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The use of hypnosis in police practice probably dates back to at least the 1780s when, based on the work of Franz Anton Mesmer, the Marquis de Puységur famously hypnotized a person, Victor, and found that he showed astonishing clairvoyance. By the 1840s, police solicited the aid of an alleged clairvoyant who purportedly disclosed the identity of a thief under hypnosis (Gravitz, 2006;Ramsland, 2008). Following the lead of the Maryland Court of Special Appeal in 1968 (Harding v. State, 1968;Martin, 2004), there has been an upsurge in the use of hypnosis for memory refreshment in criminal investigations (McConkey, 1995;also see Martin, 2004).…”
Section: Ad Antequitem Fallacymentioning
confidence: 99%
“…The use of hypnosis in police practice probably dates back to at least the 1780s when, based on the work of Franz Anton Mesmer, the Marquis de Puységur famously hypnotized a person, Victor, and found that he showed astonishing clairvoyance. By the 1840s, police solicited the aid of an alleged clairvoyant who purportedly disclosed the identity of a thief under hypnosis (Gravitz, 2006;Ramsland, 2008). Following the lead of the Maryland Court of Special Appeal in 1968 (Harding v. State, 1968;Martin, 2004), there has been an upsurge in the use of hypnosis for memory refreshment in criminal investigations (McConkey, 1995;also see Martin, 2004).…”
Section: Ad Antequitem Fallacymentioning
confidence: 99%